The Effect of Before and After Counterpressure Massage on Taste Reduction Pain of Maternal When the Phase I is Active at the Nurhasah Midwife Clinic - Mardiah (PT Inovasi Pratama Internasional, 2022)
Labor pain is a major concern for every pregnant woman because if the pain is not resolved there will be an impact on the delivery process. Labor pain can result in loss of emotional control that leads to mood disorders. Nurhasanah Midwife Clinic is a midwifery clinic located in Tembung, a Delima midwife with an average birth rate of 10-20 people per month in one month. The type of research used by the researcher is an Experiment using a Quasy Experimental design with a pretest-posttest design approach, namely research that aims to explain something and the relationship between something and another from an event that occurs because of the results of the action. Consecutive sampling is a sampling method by selecting samples that meet the research criteria for a certain period of time so that the number of samples is met. The results of this study indicate that counterpressure massage technique is effective for reducing labor pain. Labor pain is a physiological thing that makes mothers feel pain and fear in the face of childbirth. One way to make the mother feel comfortable is to give a counterpressure massage technique during contractions. Counterpressure massage given to pregnant women during the active phase I will make the mother able to control pain without having to give excessive verbal responses and can reduce the use of therapy. Pharmacological agents that have side effects for both mother and fetus.